Plasma Membrane Organization of Epidermal Growth Factor Receptor in Resting and Ligand-Bound States - Bag, Nirmalya (Biophys J, 2015)
The spatial arrangement of the epidermal growth factor receptor (EGFR) on the cellular plasma membrane is one of the prime factors that control its downstream signaling pathways and related functions. However, the molecular organization, which spans the scale from nanometers to micrometer-size clusters, has not been resolved in detail, mainly due to a lack of techniques with the required spatiotemporal resolution. Therefore, we used imaging total internal reflection-fluorescence correlation spectroscopy to investigate EGFR dynamics on live CHO-K1 plasma membranes in resting and ligand-bound states. In combination with the fluorescence correlation spectroscopy diffusion law, this provides information on the subresolution organization of EGFR on cell membranes. We found that overall EGFR organization is sensitive to both cholesterol and the actin cytoskeleton. EGFR in the resting state is partly trapped in cholesterol-containing domains, whereas another fraction exhibits cholesterol independent trapping on the membrane. Disruption of the cytoskeleton leads to a broader range of EGFR diffusion coefficients and a reduction of hop diffusion. In the ligand-bound state we found a dose-dependent behavior. At 10 ng/mL EGF the EGFR is endocytosed and recycled to the membrane, whereas diffusion and organization do not change significantly. At 100 ng/mL EGF the EGFR forms clusters, which are subsequently internalized, whereas outside the clusters diffusivity increases and the organization of the receptor remains unchanged. After disruption of cholesterol-containing domains or actin cytoskeleton, EGF induces microscopic EGFR clusters on the membrane and endocytosis is inhibited.